EFFECT OF DIFFERENT DOSES OF Γ-IRRADIATION ON THE GROWTH AND DEVELOPMENT OF PLANTS OF THE FIRST AND SECOND YEAR OF GROWING CARROTS (DAUCUS CAROTA L.) - Pidlubenko , Л.; Ovchinnikova , О. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
The effective doses of γ-irradiation for expanding the spectrum of genetic variability of carrot plants (Daucus carota L.) were determined by field, laboratory, calculation and statistical methods. Based on the results of practical research in 2020-2022, a comprehensive study was conducted for the agroclimatic zone of the Left-Bank Forest-Steppe of Ukraine to determine effective and lethal doses of γ-irradiation to expand the spectrum of genetic variability of carrot plants Daucus carota L. of two varieties of the Institute of Vegetable and Melon Growing of the National Academy of Agrarian Sciences of Ukraine, namely Nantska Kharkivska and Yaskrava. The regularities of the peculiarities of the aftereffect of physical mutagenesis (γ-irradiation) on the genotype and phenotypic manifestation of some quantitative traits of carrot (germination, size, and shape of inflorescences of plants of the second year) were established. The level of influence of physical mutagenesis on the manifestation of seed germination (laboratory and field) depending on the dose of γ-irradiation and the selected carrot variety was determined. Differences in the laboratory and field germination of seeds of carrots Nantska Kharkivska and Yaskrava after treatment with γ-irradiation and without treatment were found. Phenotypic changes in the formation of carrot inflorescences in the second year of cultivation depending on the radiation dose were revealed. The effective and lethal doses of the selected physical mutagen were determined by analyzing the mutagenic effect of γ-irradiation on the sowing qualities of carrot seeds of Nantska Kharkivska and Yaskrava varieties. The lethal doses for both varieties were 170 and 200 mR, since exposure to such doses of radiation reduced the field germination of carrot seeds to 0%, which made it impossible to obtain root crops and, accordingly, seed breeding material for further study, research and introduction into the breeding process.